A pure variation of risk in first-price auctions - Oliver Kirchkamp; J. Philipp Reiss; Abdolkarim Sadrieh (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2006)
We introduce a new method of varying the risk that bidders face in rst-price private value auctions. We nd that decreasing bidders risk signi cantly reduces the degree of overbidding relative to the risk-neutral Bayesian-Nash equilibrium prediction. This implies that risk aects bidding behavior as generally expected in auction theory. While resolving a long-standing debate on the eect of risk on auction behavior, our results give rise to a new puzzle. As risk is diminished and overbidding decreases for most of the value range, a signi cant degree of underbidding sets in for very low values.
Keywords: C92; D44; 330; risk; first-price auctions; risk-aversion; overbidding; Auktionstheorie; Risiko; Risikoaversion